Validitas Modul Sistematika Invertebrata sebagai Media Pembelajaran bagi Mahasiswa - Hasanah, Uswatun (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2024)
The aim of this research is to determine the validity of the invertebrate systematics module. This type of research is development research. The research and development model used is a 4D model modified to 3D, namely Define, Design and Develop. The research instrument used was a validation sheet. The data collection technique uses validation by validators consisting of content/material experts, display experts and language experts. The data analysis technique used is the percentage technique. Based on the results of module validation by validators, it was found that 87.5% of language experts, 87.5% of material experts, and 90% of display experts, with an average of 88.3%. Thus, the module is declared very valid and suitable to be used as a reference source for teaching materials for Invertebrate Systematics.